If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + 5y = 9y Solving 24 + 5y = 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 24 + 5y + -9y = 9y + -9y Combine like terms: 5y + -9y = -4y 24 + -4y = 9y + -9y Combine like terms: 9y + -9y = 0 24 + -4y = 0 Add '-24' to each side of the equation. 24 + -24 + -4y = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -4y = 0 + -24 -4y = 0 + -24 Combine like terms: 0 + -24 = -24 -4y = -24 Divide each side by '-4'. y = 6 Simplifying y = 6
| 8x+3(2x-1)=5x+6 | | 22=2w-8 | | 3(x-4)=5(x-6) | | K-9=-11 | | 4x+5(5/2)=15 | | 1-2(x-1)=x+6 | | -12=2+h | | 4(-3)+5y=15 | | -9w+3= | | 3x-5(0)=8 | | 3(1)-5y=8 | | 4x-9y=-15 | | 5+4.5= | | 2x^2-3bx+b^2=0 | | -16t^2+80t+224=0 | | 5+4.5=9 | | -2x+6=5x-2y | | 3x^2+12y=3 | | log(x+5)+log(x)=2 | | 20-3x=x-5 | | 3x^2+12y=1 | | log(x^2+5x)=2 | | X+3(x-1)=5(x-1)+x | | -10+7y-4y-24=1+10y | | 90=4x-3x+3x-12 | | 4(3)-4y=15 | | 30x^2+10y-20=0 | | 9h-29=5(5h+7) | | 8x-25=6x+15 | | 2+bx=b-3 | | (2x+5)/(-25)=-2.5 | | f(-3)=3(-3)+4 |